OPTIMIZING THE ROLE OF SOCIAL SCIENCES IN BUILDING STUDENT CHARACTER ACCORDING TO THE PANCASILA PROFILE - Marsini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to examine how to optimize the role of social sciences in building student character in accordance with the profile of Pancasila in high school. Through qualitative methods involving in-depth interviews, observations, and documentation studies, this study found that the integration of Pancasila values in social science learning has begun to be applied by teachers, although there are still challenges, such as limited time and low student motivation. Project-based learning methods and real activities in the community have proven to be effective in helping students understand and internalize the values of Pancasila. In addition, a supportive school environment and clear school policies play an important role in shaping the character of students. However, barriers such as limited resources and institutional support remain major challenges. The conclusion of this study confirms that optimizing the role of social sciences in building students' character requires a holistic approach, including interactive learning, school environment support, and supportive policies. Thus, Pancasila-based character education can be implemented more effectively to form a generation that is not only academically intelligent, but also has a strong character in accordance with Pancasila values.